1998
DOI: 10.1093/ajcp/110.3.334
|View full text |Cite
|
Sign up to set email alerts
|

The TEST 1 Automated System: A New Method for Measuring the Erythrocyte Sedimentation Rate

Abstract: A b s t r a c tWe evaluated performance of the TEST 1 (SIRE Analytical Systems, Udine, Italy)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
57
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 4 publications
(6 reference statements)
8
57
1
Order By: Relevance
“…The Bland and Altman plot ( fi g. 2 ), on the other hand, displayed a considerable lack of agreement between the two ESR methods, with discrepancies of up to 38 mm/h. Our fi ndings are similar to those from previous reports [7][8][9][10][11] , where a strong correlation exists between the two ESR methods using Pearson's regression analysis but not with the Bland and Altman statistical approach. However, it is widely accepted that the Bland and Altman approach is more accurate than the regression analysis [7,12,13] .…”
Section: Discussionsupporting
confidence: 91%
“…The Bland and Altman plot ( fi g. 2 ), on the other hand, displayed a considerable lack of agreement between the two ESR methods, with discrepancies of up to 38 mm/h. Our fi ndings are similar to those from previous reports [7][8][9][10][11] , where a strong correlation exists between the two ESR methods using Pearson's regression analysis but not with the Bland and Altman statistical approach. However, it is widely accepted that the Bland and Altman approach is more accurate than the regression analysis [7,12,13] .…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it can be a potentially useful alternative tool in performing ESR determination especially in a setting where the rate of bloodborne infectious diseases is rather high such as in Thailand. Indeed, the similar results from the evaluation studies on the other automated ESR have been reported (7)(8)(9). Our study can fulfill those studies and confirm the feasibility of using the automated ESR in general practice (7)(8)(9).…”
Section: Discussionsupporting
confidence: 88%
“…10,11 while some authors like Caswellet al 11 have showed low agreement values with the Westergren ESR; other shave showed a good correlation and agreement results with the same method. 12 In a similar analysis of the fully automated system, Alfadhli et al showed low-agreement results with the higher ESR values and comparable results in the normal ESR range.…”
Section: Discussionmentioning
confidence: 87%
“…The modifications introduced include the use of unopened blood collection tubes, vacuum-controlled aspiration of the sample (which intends to provide a correct dilution with the anticoagulant) and automated mixing. [5][6][7][8] Due to the rise in the prevalence of diseases such as hepatitis B and HIV, transmitted by blood, safety precautions against contamination of laboratory personnel are imperative. Using an automatic analyzer such as VesMATIC cube80™ is one evolutionary step in this regard.…”
Section: Discussionmentioning
confidence: 99%